(untitled) (Kairaranga, 2008)
This article is an analysis of the work submitted to the Ministry of Education by teams and mentors who took part in the autism spectrum disorder participatory action research (ASD PAR) project. The key findings are grouped under four themes and highlight the value of: team work; positive attitudes; using participatory action research in real-life settings; and learning together as a team.